Role of microorganisms in bioleaching of rare earth elements from primary and secondary resources - Fathollahzadeh, H.; Eksteen, J.; Kaksonen, A.; Watkin, Elizabeth (Springer, 2018)
In an era of environmental degradation, and water, and mineral scarcity, enhancing microbial function in sustainable mining has become a prerequisite for the future of the green economy. In recent years, the extensive use of rare earth elements (REEs) in green and smart technologies has led to an increase in the focus on recovery and separation of REEs from ore matrices. However, the recovery of REEs using traditional methods is complex and energy intensive, leading to the requirement to develop processes which are more economically feasible and environmentally friendly. The use of phosphate solubilizing microorganisms for bioleaching of REEs provides a biotechnical approach for the recovery of REEs from primary and secondary sources. However, managing and understanding the microbial-mineral interactions in order to develop a successful method for bioleaching of REEs still remains a major challenge. This review focuses on the use of microbes for the bioleaching of REEs and highlights the importance of genomic studies in order to narrow down potential microorganisms for the optimal extraction of REEs.